Impact of social influence in English proficiency and performance in English examinations of mathematics students from a Sino-US undergraduate education program - Zhang, Hong; Apeanti, Wilson Osafo; Ma, Liqiong; Lu, Dianchen; Zheng, Xizhong; Georgescu, Paul (Nonlinear Analysis: Modelling and Control, 2020)
This study examines the influence of certain academic and demographic variables upon the academic performance of Chinese students enrolled in a cooperative Bachelor’s degree program in Pure and Applied Mathematics. The program is English taught and jointly organised by Jiangsu University, China and Arcadia University, USA. Data from a sample of 166 students is processed using inferential and path analysis, as well as mathematical modelling. As evidenced by the inferential and path analysis, no steady improvement in the English proficiency of students has been observed, while the latter has been found to be influenced by gender and to strongly influence academic performance in Mathematics courses. The effects of negative social influences are assessed via a qualitative analysis of the mathematical model. Threshold quantities similar to the basic reproduction number of mathematical epidemiology have been found to be stability triggers. Possible interventional measures are discussed based on these findings.